PENERAPAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN KEMAMPUAN ANALISIS GEOGRAFIS PESERTA DIDIK - Juli Putra Sinambela; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The primary objective of this research was to describe the implementation of the Problem-Based Learning (PBL) model to enhance the geographical analysis ability of sixth-grade students in science and social studies at SD Negeri 2 Harian. The study, conducted over three meetings, utilized authentic problems concerning the characteristics of the six continents, contextualized with the local environment of Lake Toba. PBL was executed through five core stages: problem orientation, group organization, independent and group investigation, product development/presentation, and evaluation. Digital technologies, including Google Classroom, YouTube Edu, and Google Slides, were integrated to foster interaction and digital literacy. The results indicate a significant improvement in students' ability to recognize continents, analyze geographical features, and correlate natural conditions with key countries. Furthermore, students demonstrated development in critical thinking, communication, and collaborative skills. Although challenges such as unstable internet and low digital literacy were encountered, they were successfully mitigated using offline media, technical scaffolding, and template provision. In conclusion, the PBL model proved effective and relevant in enhancing geographical analysis and digital literacy in the elementary school context. Keywords: Problem-Based Learning, Science and Social Studies, Geographical Analysis